Robots : The Next Generation? - Shackleton, Caroline; Turner, Nathan Paul (New YORK Cambridge University, 2014)
Robots have a long history in Japan, and a big impact on its economy. Explore Japan's cultural fascination with robots and the connections between robots and religion
Cambridge Discovery Education Interactive Readers are the next generation of graded readers - captivating topics, high-impact video, and interactive exercises designed to motivate and engage.
Glossary, Contents.
Keywords: English language; Upper-intermediate level; Robots